(untitled) (International Seven Journal of Multidisciplinary, 2023)
Water is an essential natural resource for life on Earth. Currently, one of the biggest problems affecting humanity is the scarcity of this resource, widely used by the entire population. In this perspective, ensuring the sustainability of water means ensuring its responsible use, reuse and care in maintaining its purity. Therefore, the use of rainwater is seen as one of the ecological and sustainable means to avoid a possible scarcity of a natural resource. What motivated the preparation of this work was the study on the feasibility of using rainwater to be used in concreting processes without compromising its resistance. For this, the parameters for using the samples collected at predetermined points were determined; physical-chemical analyzes of the collected water were carried out; the concrete specimens were made with potable and rainwater and compression tests were carried out to analyze the resistance of the specimens. The values obtained from the tests and trials carried out on the two samples of rainwater collected, the parameters evaluated in this study obtained through the tests already mentioned, were satisfactory and fit the standards established by the ABNT NBR 15900 standard for the use of water of the rain on the concrete kneading. DOI: 10.56238/isevmjv2n1-010